THE IMPACT OF REGULAR PHYSICAL ACTIVITY ON DELAYING THE ONSET OF ALZHEIMER’S DISEASE: A REVIEW OF NEUROPROTECTIVE MECHANISMS - Łabuzińska, Luiza; Sikorska, Laura Magdalena; Pudło, Paulina; Koman, Anna; Bukowiec, Martyna; Szałata, Karolina; Asztabski, Mikołaj (International Journal of Innovative Technologies in Social Science, 2026)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder marked by memory impairment, cognitive deterioration, and neurobiological changes, notably the accumulation of amyloid-beta (Aβ) and tau pathology.  Recent data suggests that consistent physical activity (PA) may delay the onset and progression of Alzheimer's disease (AD) through various neuroprotective mechanisms.  This research synthesizes results from 31 contemporary investigations encompassing both human and animal subjects.  The focus is on the impact of physical activity on brain-derived neurotrophic factor (BDNF) expression, cerebral blood flow, inflammation reduction, and proteinopathy management.  Brain-Derived Neurotrophic Factor (BDNF) is crucial for maintaining synaptic plasticity and promoting neurogenesis in the hippocampus, both of which are significantly compromised in Alzheimer's Disease (AD).  PA-induced elevations in BDNF enhance cognitive resilience and neuronal integrity.  Furthermore, exercise has been shown to enhance cerebral perfusion, so improving the delivery of oxygen and nutrients while promoting the disposal of waste, including glymphatic flow.  The anti-inflammatory effects of PA entail the downregulation of pro-inflammatory cytokines (e.g., IL-6, TNF-α) and the upregulation of anti-inflammatory mediators, which alleviate chronic neuroinflammation commonly seen in Alzheimer's disease.  Furthermore, PA appears to reduce oxidative stress by enhancing innate antioxidant systems, including superoxide dismutase and glutathione peroxidase.  PA may significantly affect essential pathophysiological features of AD, such as amyloid-beta buildup and tau hyperphosphorylation, by promoting proteostasis and stimulating autophagy.  Research from both preclinical and clinical studies repeatedly reveals associations between regular physical activity and improved cognitive function, augmented brain structural integrity, and less neurodegeneration.  The data indicate that physical activity serves as a cost-effective, accessible, and non-pharmacological intervention with significant neuroprotective potential to reduce the risk of Alzheimer's disease and delay its development.